Animals: britannica discovery library - Pole, Micheal (Encyclopaedia Britannica, Inc. Chicago, 2006)
Explore the diverse world of animals, from majestic mammals to vibrant sea creatures, uncovering their habitats, behaviors, and roles in our ecosystem.